Determination of surface defects by using the wavefront scanner - Goloborodko, N.S.; Grygoruk, V.I.; Kurashov, V.N.; Podanchuk, D.V.; Goloborodko, A.A.; Kotov, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The possibility of changes in the polarization state of the laser beam reflected from inhomogeneity with the refractive index gradient is theoretically shown, which allows separating the phase shifts related with relief inhomogeneities and local changes of the surface refractive index. Modification of the wavefront scanner for analyzing the wavefront of the laser beam reflected from the samples’ surface is considered. The main idea of the method is to use the focused laser beams with different polarizations for illuminating separate areas of the surface. The results of detecting test surfaces with different structures by the wavefront scanner are presented.